ERGONOMIC REVIEW IMPLEMENTATION OF MATERIALS AND CORRIDOR FLOOR FLOOR Dr. SARJITO · YOGYAKARTA - Dwi Retno Sri Ambarwati; Eni Puji Astuti (Jurnal Penelitian Saintek, 2007)
The aim of this research is  to describe how far  is  the ergonomics conditions have been applied in the applying of material and colour of the  corridor floor  at  RSVP   Dr. Sarjito  Yogyakarta, identifying problems that happened and also its cause.The approach of this research is descriptive qualitative, depicting what the existence of the circumstance of corridor floor at RSVP Dr. Sarjito Yogyakarta through observation and documentation 'and to describe the situation of research object, perceiving problems  that happened and its cause.The result of this research indicate that the floor  materialthat   isapplied is ceramic tile that is equal to 99.81 %, rubber vynil is equal to0.08% and cement plaster  is equal to 0.106% from  entire corridor floor  that becoming the research object. Colour of the floor is white that combined by old grey textured ceramic tile. Evaluated from the ergonomics conditions  including  the security, safety  and comfort aspect, ceramic floor that used at the corridor of RSVPDR.SARJITO havefulfilled the conditions. The esthetic conditions with theprincipal consideration of composition not yet beenfullfiled because there an; no variation ofform,  colour and motive. Motive, form and colour are monoton and also there are no emphasis that will attract the attention, make thefeeling bored especially whenfringing at a long corridor,so that the distancefelt farther.